Lattice theory. - Donnellan, Thomas (Commonwealth and international library. Mathematics division., 1968)
Lattice Theory presents an elementary account of a significant branch of contemporary mathematics concerning lattice theory. This book discusses the unusual features, which include the presentation and exploitation of partitions of a finite set.